European Anthropology - Ochilov Farrukh Ganijonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the new era, the XVIII-XIX centuries included the views and research of scientists of European antiquity on the ancient world.